Integrating Gamification into Skimming and Scanning Strategies to Enhance English as a Foreign Language (EFL) Students’ Reading Test Performance - Eka Roswida Anggraini; Yuliyanto Sabat; Laili Hibatin Wafiroh (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
Passive reading habits and limited strategic comprehension under timed conditions remain persistent challenges in Indonesian EFL classrooms, underscoring the urgent need for more purposeful and engaging instructional approaches. This study examined the effectiveness of integrating gamification into skimming and scanning instruction to improve EFL students' reading test performance through a quasi-experimental design. Two intact classes of eighth-grade students were compared, where the experimental group taught with Wordwall-based gamified activities and the control group with conventional instruction. Results revealed that the experimental group achieved significantly higher gains in reading speed, accuracy, and comprehension, supported by statistical evidence (t = 12.334, p < 0.001; Cohen’s d = 0.851). Classroom observations further documented marked improvements in engagement, participation, motivation, reading speed, and accuracy throughout the intervention. These results demonstrate that gamified digital instruction provides a reliable, theoretically grounded, and replicable pedagogical scaffold for fostering strategic reading competency, particularly within Indonesian junior high school contexts.